PEMIKIRAN DAN PERADABAN ISLAM PADA MASA KHULAFAUR RASYIDIN - Jajang; Iwan Hermawan; Lismawati; Lilis Fauziyah; Masripah; M. Tajudin Zuhri; Nenden Munawaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses Islamic thought and civilisation during the reign of Khulafaur Rasyidin which consisted of four caliphs after the death of Rosulallah SAW, namely Abu Bakar As-Siddiq, Umar bin Khattab, Usman bin Affan, and Ali bin Abi Talib. This research uses a qualitative approach with a library research method, carried out by collecting various data sources both books, journals, papers, articles, and sources that are relevant to the discussion studied. The Khulafaur Rasyidin period was an important transitional era in Islamic history by prioritising the values of deliberation, leadership, and justice in accordance with Islamic law. Each caliph has a unique character in his leadership, but still adheres to the benefit of the people, the spread of Islamic preaching, strengthening the government structure and through his thoughts the caliphs can realise the development of Islamic civilisation. The Khulafaur Rashidin made very important contributions to future Muslims in the codification of the Qur'an, territorial expansion, the establishment of government systems and the emergence of political conflicts that tested the unity of Muslims.  The Khulafaur Rasyidin period became the main foundation for the future glory of Islam and provided examples or instructions in managing the government system that adhered to Islamic values.